Learned helplessness in the rat: improvements in validity and reliability - Vollmayr, Barbara; Henn, Fritz A. (Brain research. Brain research protocols, 2001)
Major depression has a high prevalence and a high mortality. Despite many years of research little is known about the pathophysiologic events leading to depression nor about the causative molecular mechanisms of antidepressant treatment leading to remission and prevention of relapse. Animal models of depression are urgently needed to investigate new hypotheses. The learned helplessness paradigm initially described by Overmier and Seligman [J. Comp. Physiol. Psychol. 63 (1967) 28] is the most widely studied animal model of depression. Animals are exposed to inescapable shock and subsequently tested for a deficit in acquiring an avoidance task. Despite its excellent validity concerning the construct of etiology, symptomatology and prediction of treatment response [Clin. Neurosci. 1 (1993) 152; Trends Pharmacol. Sci. 12 (1991) 131] there has been little use of the model for the investigation of recent theories on the pathogenesis of depression. This may be due to reported difficulties in reliability of the paradigm [Animal Learn. Behav. 4 (1976) 401; Pharmacol. Biochem. Behav. 36 (1990) 739]. The aim of the current study was therefore to improve parameters for inescapable shock and learned helplessness testing to minimize artifacts and random error and yield a reliable fraction of helpless animals after shock exposure. The protocol uses mild current which induces helplessness only in some of the animals thereby modeling the hypothesis of variable predisposition for depression in different subjects [Psychopharmacol. Bull. 21 (1985) 443; Neurosci. Res. 38 (200) 193]. This allows us to use animals which are not helpless after inescapable shock as a stressed control, but sensitivity, specificity and variability of test results have to be reassessed.